Exploring the mechanism of tetramethylpyrazine in the treatment of osteoarthritis based on network pharmacology - Li, Juncen; Song, Daiying; Li, Bohui; Wang, Yajie; Sun, Huilin; Li, Qinglin; Lin, Xiangming; Wang, Di; Zhou, Guangdong; Liu, Yu (Frontiers in Chemistry, 2024)
Background: Osteoarthritis(OA) is the most common joint disease, which mainly damages articular cartilage and involves the whole joint tissue. It has the characteristics of long course, repeated symptoms and high disability rate, and the incidence trend is gradually increasing. Tetramethylpyrazine(TMP) is the main alkaloid active substance in Ligusticum wallichii, a traditional Chinese medicine, which has the effect of promoting blood circulation and dredging collaterals, and has a good effect on the treatment of early OA, but its molecular mechanism has not been fully clarified so far. Based on network pharmacology, molecular docking simulation and animal experiments, this study explored the target and molecular mechanism of TMP in the treatment of OA.We used PubChem, SwissTargetPrediction, and PharmMapper databases to predict the molecular structure and potential targets of TMP. GeneCards and DisGeNET databases were used to predict the relevant targets of OA. Apply UniProt database to convert targets into unified gene names, and proofread and remove duplicate gene names. The intersection targets of TMP and OA obtained on venny2.1.0 website were submitted to the STRING database to construct a PPI network. CytoScape 3.8.2 software was used to analyze the PPI network and obtain the sub-network modules and 10 key targets. The intersection targets of TMP and OA were analyzed by Kyoto